Applications of indocyanine green in robotic urology. Issue 4 (December 2016) - Bates, Anthony; Patel, Vipul
Abstract Indocyanine green is a fluorescent molecule with wide ranging applications in minimally invasive urological surgery. This article explores the utility of ICG assisted intraoperative fluorescence in robotic urology.